2018
DOI: 10.1089/jwh.2017.6555
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Urgency in Working Women: What Factors Are Associated with Urinary Urgency Progression?

Abstract: Losing urine with defecation and making the bladder empty faster by pushing down should be explored as intervention targets to prevent women from progressing from Stage 3 to Stage 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…often or always vs. never, occasionally, or sometimes), representing habitual behavior. 9 In addition, women responded to a single item about limiting fluid intake: “Do you cut down on the amount of fluid you drink so that your urinary symptoms improve?” (Never, Occasionally, Sometimes, Most of the time, All of the time). 10…”
Section: Methodsmentioning
confidence: 99%
“…often or always vs. never, occasionally, or sometimes), representing habitual behavior. 9 In addition, women responded to a single item about limiting fluid intake: “Do you cut down on the amount of fluid you drink so that your urinary symptoms improve?” (Never, Occasionally, Sometimes, Most of the time, All of the time). 10…”
Section: Methodsmentioning
confidence: 99%
“…Many factors are associated with UI [ 8 ], including unmodifiable factors (e.g., age, gender, menopause, history of vaginal delivery) and potentially modifiable factors (e.g., smoking, alcohol intake, toileting behaviors [ 9 ], constipation, and obesity). Besides UI’s impact on women’s physical and mental health, UI affects women’s quality of life by limiting social activities [ 10 ] and interactions, interfering with the ability to work [ 11 ], and increasing the financial burden on women and society [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, at least one qualitative study showed a gap in information on pelvic floor disorders among African American and Latin American women, despite a demand for health education. Other studies have explored adult women's experiences of bladder sensations (Heeringa, de Wachter, van Kerrebroeck, & van Koeveringe, 2011;De Wachter, Heeringa, van Koeveringe, & Gillespie, 2011;Zhou, Newman, & Palmer, 2018) associated with LUTS, such as urinary tract infections (Baerheim, Digranes, Jureen, & Malterud, 2003), recurrent cystitis (Alraek & Baerheim, 2001) and overactive bladder (OAB) (Heeringa, van Koeveringe, Winkens, van Kerrebroeck, & de Wachter, 2012).…”
Section: Backg Rou N Dmentioning
confidence: 99%